LANSKAP MODERASI KEAGAMAAN SANTRI, REFLEKSI POLA PENDIDIKAN PESANTREN - Saifudin Asrori (FISIP UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. Positioning a pesantren in a series of continuum lines between liberals and conservatives, based on critical interpretations of religious texts as opposed to rigid and liberal understandings, is a misunderstanding of the landscape of religious moderation. This article elaborates on the complex process of Islamic boarding school understanding and practice in the midst of a religious shift towards a conservative direction. Through literature study based on a reading model based on maslahah on religious texts and the essence of religious texts based on the plurality of views of the schools of thought conducted by the Pondok Modern Darussalam Gontor. This article concludes that through preserving values through Pancajiwa and the motto of the pesantren, the integration between formal and informal curricula places Gontor's position as a moderate educational institution.Keywords: Islamic Moderation, Maslah, curriculum, PMDG, Indonesia. Abstrak. Memposisikan sebuah pesantren dalam rangkaian garis kontinum antara liberal dan konservatif, berdasarkan penafsiran kritis atas teks keagamaan sebagai lawan pemahaman kaku dan liberal, menjadi salah upaya memahami lanskap moderasi keagamaan. Artikel ini mengelaborasi proses kompleks pemahaman dan praktik keagamaan pesantren di tenggah pergeseran keagamaan ke arah konservatif. Melalui studi pustaka berdasarkan model pembacaan berdasarkan maslahah atas teks-teks keagamaan dan inti dari teks keagamaan berdasarkan pluralitas pandangan madzhab yang dilakukan oleh Pondok Modern Darussalam Gontor. Artikel ini menyimpulkan bahwa nilai-nilai dilestarikan melalui pancajiwa dan motto pesantren, intergrasi antara kurikulum formal dan informal menempatkan posisi Gontor sebagai lembaga pendidikan yang moderat. Kata Kunci: Moderasi Islam; Maslahah; Kurikulum; PMDG; Indonesia.